Roles of social capital resources in science and technology activity of scientific working groups - Giang, Nguyen Thi Huong (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2019)
Scientific collaboration is considered a cornerstone of 21st Century Science and a spring board for economic prosperity. Collaboration is believed to be influential on researchers’ productivity. At a more basic level, it is also considered to be a fundamental part of the development of scientific human capital. Scientific collaboration is facilitated through social capital. Through a series of collaborative interactions, scientists move to positions within collaboration networks, which in turn creates value for scientific working group as well as individuals in that group. The aim of this study is to evaluate the role of social capital in science and technology activities of scientific working groups (SWGs), including the case of Hanoi National University excellent scientific working group. Code: 19013101